Gastronomy unravelled by physics: Gastrophysics. (1st October 2021) - Pedersen, Mie Thorborg; Hansen, Per Lyngs; Clausen, Mathias Porsmose
Useful attempts to shed light on the nature of gastronomy from a scientific point of view and to unravel the crucial connection between food, eating and well-being are currently underrepresented in the scientific literature. However, several scientific disciplines ranging from the natural to the social sciences offer valuable new perspectives on gastronomy. As one of the key disciplines in natural science, physics offers original and rigorous perspectives on all processes and structures constrained by the laws of nature. The emerging discipline called gastrophysics employs the full range of concepts, techniques and methods from physics to generate useful scientific input to the complex and holistic reflections on gastronomy. Relying on a review of the existing literature, this article illustrates how a science-based gastrophysics emerges, to a large extent from the convoluted history of food science as well as from various recent ‐ and often overlapping ‐ attempts to combine modern scientific methodology to questions from gastronomy. However, the present review also insists on a physics-inspired methodology to handle scale and complexity in food preparation and consumption across length scales from sub-molecular to entire foods. We exemplify how gastrophysics directly helps to develop gastronomy and how it adds to current approaches in traditional food science. We also suggest that gastrophysics may prove relevant in the context of the ongoing food transformation, which focuses strongly on sustainability, but where the importance of gastronomic aspects in this transformation is greatly needed.